Tantangan IMT-GT Dalam Meningkatkan Penanaman Modal Asing Provinsi Jambi Tahun 2017-2021 - Feby Rachma Alfi Dhiandra; Dudy Heryadi; Laode Muhammad Fathun (ITB AAS INDONESIA, 2023)
Indonesia Malaysia Thailand-Growth Triangle (IMT-GT) is an economic cooperation forum participated by Jambi Province. IMT-GT functions as an investment facilitator, and the goal is to connect Jambi Province with potential investors. The use of qualitative methodologies in this study will significantly assist the author in knowing and explaining the dynamics of the challenges of IMT-GT as a KESR forum in increasing foreign investment in Jambi Province in 2017–2021, along with the opportunities and challenges faced by IMT-GT in the process. The results of the study show that there is an IMT-GT framework for the period 2017-2021 found challenges that affect the dynamics of economic growth in Jambi Province, such as Thailand's inability to invest in Jambi Province for financial reasons, the Covid-19 pandemic that affects the global economy, and Jambi Province is assessed still does not facilitate investors to enter. This study aims to discuss the challenges faced by IMT-GT during cooperation in Jambi Province; the period chosen is the initial treatment of the 2017-2021 IMT-GT IB framework. Varies every year, as well as in Malaysia and Thailand. However, Thailand's economic growth tends to be lower than Indonesia and Malaysia’s